(untitled) (Journal of the College of Basic Education, 2024)
This research aims to identify (the role of the teacher and the learner in the mobile correspondent strategy). To determine the role of the teacher, the researcher was keen to limit the roles of the teacher and the learner in implementing the correspondent strategy. These roles become clear through the following roles: The learner plays the role of the mobile correspondent, provided that this role is played by one learner from among The group is individualized and can be changed sequentially. The learner assigned to the role of the mobile correspondent discusses with members of the other educational groups, and also summarizes the information he learns from the other groups to discuss with the members of his original group. After determining what the teacher and learner do in the mobile correspondent strategy, the researcher concluded that the role of the teacher and learning It consists of collecting information from other educational groups and classifying it, that is, the information each group summarizes individually in order to arrive at the best opinions and experiences that he has seen in order to convey it to his group. The teacher plays an effective and important role during the implementation of the mobile correspondent strategy, despite the great difference between his role in this strategy. Its role is in regular teaching, but it plays important roles for the success of implementing the steps of the strategy during application. The researcher recommends holding a workshop for teachers to clarify the role of the teacher and the learner on the roles of the teacher and the learner in the mobile learning strategy. He also suggested conducting a study that addresses the effectiveness of the teacher’s role in the mobile learning strategy.